Chelating properties of EDTA-type ligands containing six-membered backbone ring toward copper ion: Structure, EPR and TD-DFT evaluation. (9th March 2017) - Ćendić, Marina; Deeth, Robert J.; Meetsma, Auke; Garribba, Eugenio; Sanna, Daniele; Matović, Zoran D.
Graphical abstract: The [Cu(1, 3-pdta-type)] n − complexes with diverse 1, 3-propanediaminetetracarboxylate chelates have been investigated. Results of structural, spectral and computational (LFMM, DFT and TD-DFT) analysis are indicative for a good candidates being selective chelating drugs against excess of copper found in living organisms. Abstract: The P-APC ligands (EDTA-like aminopolycarboxylate ligands comprising 1, 3-propanediamine backbone) H4 pdta, H4 pd3ap, H4 pddadp and H4 pdtp (H4 pdta = 1, 3-propanediamine- N, N, N ′, N ′-tetraacetatic acid; H4 pd3ap = 1, 3-propanediamine- N, N, N ′-triacetic- N ′-3-propionic acid; H4 pddadp = 1, 3-propanediamine- N, N ′-diacetatic- N, N ′-di-3-propionic acid; H4 pdtp = 1, 3-propanediaminetetra-3-propionic acid) were investigated. The chelating ligands coordinate to copper(II) via five or six donor atoms affording distorted trigonal-bipyramid and octahedral structures that were verified by X-ray analysis for Ba[Cu(pd3ap)]·6H2 O (1 ) and trans (O6 )-Ba[Cu(pddadp)]·8H2 O (2 ) complexes respectively. The impact of counter-ions on the P-APC complexes is shown in detail together with the analysis of another strain parameters. EPR spectral results confirm the penta-coordination of1 and hexa-coordination of2 in aqueous solution, even if several Cu(II) species with different protonation degree exist as a function of pH, and indicate that a hexa-coordinated structure is favored when the two axial COO − donors close five-membered chelate rings. We also present here the results of molecular mechanics (LFMM) calculations based on our previously-developed force field along with results of DFT (Density Functional Theory). On the basis of extensive DFT and TD-DFT calculations the B1LYP/6-311++G(d, p) level has been seen as an accurate theory for calculating and predicting the UV–Vis spectra in case of copper–P-APC compounds.